1986
DOI: 10.1002/dev.420190312
|View full text |Cite
|
Sign up to set email alerts
|

Visually imprinted maternal preference in ducklings is redirected by social interaction with siblings

Abstract: This study examined the influence of social interaction with broodmates on a visually imprinted maternal preference in domestic mallard ducklings (Anas platyrhynchos) during the first three days of postnatal life. Twenty-four-hour-old ducklings were allowed to follow a stuffed mallard hen for 30 min. This experience resulted in a visually imprinted preference for the familiar stuffed hen over 4 stuffed ducklings in simultaneous choice tests at 48 and 72 hr after hatching, but only if the imprinted birds were k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 20 publications
(14 reference statements)
3
19
0
Order By: Relevance
“…The presence of a sibling from birth could delay or weaken the process of attachment to the mother. It has been shown in ducklings that social interaction with siblings can redirect preference for the mother (Lickliter & Gottlieb, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a sibling from birth could delay or weaken the process of attachment to the mother. It has been shown in ducklings that social interaction with siblings can redirect preference for the mother (Lickliter & Gottlieb, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the social effect was not clear because the imprinting response probability in group P was not particularly different from that of group I. Previous investigators (Johnston & Gottlieb, 1985;Lickliter & Gottlieb, 1985, 1986) have reported that although social interaction with age mates up to 48 h after hatching did not interfere with the original maternal preference, the same experience between 38 h and 72 h actively interfered with preference for the mallard model. Thus, we can conclude that up to 48 h after hatching, with the original stimulus being either a natural or an artificial object, social interaction after the primary imprinting does not interfere with the maintenance of primary imprinting.…”
Section: Discussionmentioning
confidence: 85%
“…Thus, each brood included an 'experimental' male reared with heterospecific females and a 'control' male reared with females of his own species. It was not possible to form larger broods or rear ducklings with adult females owing to logistical constraints, but previous work has demonstrated that interaction with siblings contributes to both filial (Lickliter & Gottlieb 1986) and sexual (Schuetz 1965;Cheng et al 1978) imprinting in Anas ducklings. Broods were reared in visual isolation in outdoor enclosures with ad libitum access to food, water and shelter.…”
Section: Methodsmentioning
confidence: 99%